2022
DOI: 10.1186/s12891-022-05727-6
|View full text |Cite
|
Sign up to set email alerts
|

Lower rate of acceptable knee function in adolescents compared with young adults five years after acl reconstruction: results from the swedish national knee ligament register

Abstract: Background The number of studies with a large cohort of patients that primarily focus on patient-reported outcomes after ACL reconstruction in children and adolescents is limited. The purpose of the present study was to determine whether patient age affects the proportion of patients that achieve a patient-acceptable symptom state (PASS) on the Knee injury and Osteoarthritis Outcome Score (KOOS) subscales one, two, five and 10 years after an ACL reconstruction. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 30 publications
2
8
0
Order By: Relevance
“…Noncompleters at follow-up were more often male and younger, which is consistent with previous reports [32,39]. Although the pattern of missingness may skew the results in both directions [40,41], the risk of selection bias can be estimated to be minor as differences in preoperative KOOS scores were trivial (mean differences <3 points).…”
Section: Key Components Of the Treatment Algorithmsupporting
confidence: 88%
“…Noncompleters at follow-up were more often male and younger, which is consistent with previous reports [32,39]. Although the pattern of missingness may skew the results in both directions [40,41], the risk of selection bias can be estimated to be minor as differences in preoperative KOOS scores were trivial (mean differences <3 points).…”
Section: Key Components Of the Treatment Algorithmsupporting
confidence: 88%
“…Similar to the results of the present study, previous studies have shown that younger patients report higher scores on the ACL-RSI compared with adults [ 32 ]. Younger patients have previously also been shown to be more content than adults with their knee function 1 year after ACL reconstruction [ 12 ], but the opposite findings have also been reported 2, 5 and 10 years after ACL reconstruction [ 26 ]. A recent study from the same patient registry showed that patients who had greater psychological readiness, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Young patients have been reported to have a high rate of return to sport (RTS) after anterior cruciate ligament (ACL) reconstruction [ 3 , 16 , 19 ]; however, early RTS has also been associated with a high rate of graft rupture and contralateral ACL injury [ 16 ]. Adolescents have reported a lower rate of acceptable knee function after ACL reconstruction and run an increased risk of sustaining a second ACL injury compared with their older counterparts [ 26 , 27 ]. In addition, adolescents have previously been reported to return to knee-strenuous sports earlier than young adults, without having recovered acceptable knee function after ACL reconstruction [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Results from the Swedish National Knee Ligament Register demonstrated that adolescents reported a lower score than young adults on the Knee injury and Osteoarthritis Outcome Score (KOOS) at the 2, 5, and 10-year follow-ups after an anterior cruciate ligament (ACL) reconstruction 74 . The reason for this is unclear, but the authors postulated that it might be due to adolescents returning to activities faster than young adults.…”
Section: Sportsmentioning
confidence: 99%